2019
DOI: 10.1021/acs.jmedchem.9b00142
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Zika Activity of a Library of Synthetic Carbohydrate Receptors

Abstract: Zika virus (ZIKV), a mosquito-borne flavivirus, is a global health concern because of its association with severe neurological disorders. Currently, there are no antiviral therapies that have been specifically approved to treat ZIKV, and there is an urgent need to develop effective anti-ZIKV agents. Here, we report anti-ZIKV activity of 16 synthetic carbohydrate receptors (SCRs) that inhibit ZIKV infection in Vero and HeLa cells. Using a ZIKV reporter virus particle-based infection assay, our data demonstrates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 87 publications
0
18
0
Order By: Relevance
“…α‐Man is a particularly important carbohydrate because of its prevalence on the surfaces of viruses [8–10] and cancer cells [2–4] . In parallel to the binding studies, we recently demonstrated the ability of these flexible SCRs to inhibit viral infection, including Zika virus, with nanomolar IC 50 values [39] …”
Section: Introductionmentioning
confidence: 87%
“…α‐Man is a particularly important carbohydrate because of its prevalence on the surfaces of viruses [8–10] and cancer cells [2–4] . In parallel to the binding studies, we recently demonstrated the ability of these flexible SCRs to inhibit viral infection, including Zika virus, with nanomolar IC 50 values [39] …”
Section: Introductionmentioning
confidence: 87%
“…1 . We selected three SCRs ( SCR001 , SCR005 and SCR007 ) that have displayed potent antiviral activity against live ZIKV [ 28 ] and seven recently synthesized SCRs ( SCR007 , SCR018 , SCR019 , SCR020 , SCR021 , SCR022 , SCR023 ) that have shown high selectivity towards biologically relevant monosaccharides [ 29 ]. All tetrapodal SCRs share the same chemical design: a biaryl core decorated with four linkers terminated with a heterocycle ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To challenge this status quo and redefine glycans as feasible targets for therapeutics and chemosensors, several research groups [ [23] , [24] , [25] ] have developed synthetic carbohydrate receptors (SCRs) – small molecules that bind carbohydrates through noncovalent interactions. Inspired by the structure and binding thermodynamics of natural glycan binding proteins, we have recently reported a series of flexible, tetrapodal SCRs based upon a biaryl core, that are selective for non-glucosides [ 13 , [26] , [27] , [28] , [29] , [30] ], and some of these tetrapodal SCRs display nanomolar inhibition against live ZIKV, with data suggesting that the mode of action is the prevention of viral attachment/binding/entry [ 13 , 28 ]. Despite these encouraging results, without a molecular-level understanding of the binding of the glycans by SCRs, their structures cannot be rationally redesigned to achieve strong and selective binding towards EnV glycans.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that this molecule is not selective to this protein, suggesting this is not its action mechanism. Furthermore, this type of molecules are key in targeting carbohydrate receptors being able to treat viral infections 32,33 . If one analyzes the Steviol binding sites 1 and 3 (Figure 6) it can be seen that in site three Steviol make 9 interactions including 3 HBs.…”
Section: Resultsmentioning
confidence: 99%